‘EVALUATION OF EFFICACY OF PERFUSION MRI IN DIFFERENTIATING HIGH GRADE GLIOMAS FROM OTHER CNS LYMPHOMAS AND SOLITARY BRAIN METASTASIS: A SYSTEMATIC REVIEW’’ - Dr. Mounika Sathi; Dr.Shivaji Pole; Dr. Devidas Dahiphale; Dr. P. S. Mishrikotkar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Treatment evaluation of patients with tumor is crucial for clinical decision-making. Conventional contrast MRI struggles to distinguish between tumor progression and treatment effects. High-grade gliomas (HGGs), primary central nervous system lymphomas (PCNSLs), and solitary brain metastasis (SBMs) often exhibit similar enhancement patterns on MR imaging and complicating diagnosis. Perfusion MRI, which provides insights into tumor vascularity and microcirculation, may improve diagnostic accuracy. This systematic review aim to assess the effectiveness of perfusion MRI in differentiating HGGs from PCNSLs and SBMs.Method: We performed this study based on the preferred reporting items for systematic review. The literature search was conducted using an electronic database for related articles published in English from PubMed, Scopus, the Web of Science, and Cochrane with periods from 2014 to 2023. Literature screening, data extraction, and risk of bias assessment were independently performed.Results: A total of 765 articles were found, with 13 studies meeting the eligibility criteria. These studies included a total of 368 HGG patients, 131 SBM patients, and 102 PCNSL patients. Most of the studies included were retrospective studies. The mean age of the enrolled patients was 61.2 years. The majority of articles demonstrated low risk (62.82%), signifying reliability, while 19.23% of the studies were classified as 'unclear,' indicating some ambiguity without invalidating the results. Studies classified as 'high risk' (17.95%) indicated substantial bias and potential errors. For analysis, relative cerebral blood volume (rCBV) was a useful parameter for differentiating HGG from PCNSL and SBM, demonstrating significantly higher rCBV values for HGG.Conclusion: Perfusion MRI is a promising non-invasive imaging method with good accuracy in diagnosing different types of brain tumors. The relative cerebral blood volume (rCBV) can facilitate the differentiation between HGG from PCNSLs and SBMs. Specifically, dynamic susceptibility contrast MRI (DSC-MRI) shows high diagnostic performance in stratifying gliomas. Keywords: HGG, SBM, Perfusion MRI, DSC-MRIBackground: Treatment evaluation of patients with tumor is crucial for clinical decision-making. Conventional contrast MRI struggles to distinguish between tumor progression and treatment effects. High-grade gliomas (HGGs), primary central nervous system lymphomas (PCNSLs), and solitary brain metastasis (SBMs) often exhibit similar enhancement patterns on MR imaging and complicating diagnosis. Perfusion MRI, which provides insights into tumor vascularity and microcirculation, may improve diagnostic accuracy. This systematic review aim to assess the effectiveness of perfusion MRI in differentiating HGGs from PCNSLs and SBMs.Method: We performed this study based on the preferred reporting items for systematic review. The literature search was conducted using an electronic database for related articles published in English from PubMed, Scopus, the Web of Science, and Cochrane with periods from 2014 to 2023. Literature screening, data extraction, and risk of bias assessment were independently performed.Results: A total of 765 articles were found, with 13 studies meeting the eligibility criteria. These studies included a total of 368 HGG patients, 131 SBM patients, and 102 PCNSL patients. Most of the studies included were retrospective studies. The mean age of the enrolled patients was 61.2 years. The majority of articles demonstrated low risk (62.82%), signifying reliability, while 19.23% of the studies were classified as 'unclear,' indicating some ambiguity without invalidating the results. Studies classified as 'high risk' (17.95%) indicated substantial bias and potential errors. For analysis, relative cerebral blood volume (rCBV) was a useful parameter for differentiating HGG from PCNSL and SBM, demonstrating significantly higher rCBV values for HGG.Conclusion: Perfusion MRI is a promising non-invasive imaging method with good accuracy in diagnosing different types of brain tumors. The relative cerebral blood volume (rCBV) can facilitate the differentiation between HGG from PCNSLs and SBMs. Specifically, dynamic susceptibility contrast MRI (DSC-MRI) shows high diagnostic performance in stratifying gliomas.